Discursive construction of Andrea Sachs’ identities in the movie “The devil wears Prada = Nghiên cứu về cách kiến tạo đặc tính cá nhân thông qua diễn ngôn của nhân vật Andrea Sachs trong bộ phim "The devil wears Prada". M.A Thesis Linguistics: - Đào, Thị Lan Trang (2019)
Undeniably, the intricate constructions of film characters’ identities have always been a noteworthy matter of research as they play an integral part in transferring film messages to the audience. One of the most attention- grabbing film in the early 21st century is “Devil wears Prada”, which has intrigued both linguists and researchers in other fields in the search for its messages and associated ideologies conveyed through its characters.